Influence of Atmospheric Transport on Estimates of Variability in the Global Methane Burden. Issue 4 (25th February 2019) - Pandey, Sudhanshu; Houweling, Sander; Krol, Maarten; Aben, Ilse; Nechita‐Banda, Narcisa; Thoning, Kirk; Röckmann, Thomas; Yin, Yi; Segers, Arjo; Dlugokencky, Edward J.
Abstract: We quantify the impact of atmospheric transport and limited marine boundary layer sampling on changes in global and regional methane burdens estimate using tracer transport model simulations with annually repeating methane emissions and sinks but varying atmospheric transport patterns. We find the 1 σ error due to this transport and sampling effect on annual global methane increases to be 1.11 ppb/year and on zonal growth rates to be 3.8 ppb/year, indicating that it becomes more critical at smaller spatiotemporal scales. We also find that the trends in inter‐hemispheric and inter‐polar difference of methane are significantly influenced by the effect. Contrary to a negligible trend in the inter‐hemispheric difference of measurements, we find, after adjusting for the transport and sampling, a trend of 0.37 ± 0.06 ppb/year. This is consistent with the emission trend from a 3‐D inversion of the measurements, suggesting a faster increase in emissions in the Northern Hemisphere than in the Southern Hemisphere. Plain Language Summary: Changes in global and regional atmospheric burdens of methane are determined by the net effect of sources and sinks and atmospheric transport. Many studies approximate the burdens based on measurements from a network of globally distributed surface air sampling sites. Here we quantify the impact of atmospheric transport and limited marine boundary layer sampling (transport and sampling) on changes in global and regional methane burden estimates using tracer transport model simulation with annually repeating methane emissions and sinks but varying atmospheric transport patterns. We find that for assessing the annual global methane increases, a measurement‐only approach is fairly accurate. However, extending the measurement‐only analysis to hemispheric or latitudinal variations is more problematic as transport influences quickly become significant or even dominant. We find a large impact of transport and sampling effect on the inter‐hemispheric and inter‐polar difference. Key Points: Transport gives rise to CH4 variations in the spatiotemporal gradients, which are not caused by source or sink changes We find the transport and sampling error on annual global CH4 increases to be 1.11 ppb/year and on zonal growth rates to be 3.8 ppb/year The transport‐adjusted inter‐hemispheric difference has a trend of 0.37 ppb/year, consistent with the emission trend from a 3‐D inversion